Successful innovation by motivation - Koudelková, Petra; Milichovský, František (Business: Theory and Practice, 2015)
Innovation is one of the most important factors for business growth. Human capital plays a significant role in the successful process of innovation. This article deals with employee motivation in the innovation process and the main scientific aim of this study is to present results of research that was undertaken in the Czech Republic at the beginning of 2013. Questionnaires were used for the survey and statistical analyses such as Chi square test or Hierarchical cluster analysis were used for data processing. This study also provides a theoretical and practical overview of business innovation in the Czech Republic.